A study of teachers’ views upon the role of other teachers in their work - work in progress - Kairen Cullen (Educate~, 2006)
Contextualisation
This research note focuses on the assumptions made about the ways in which teachers work
with their colleagues. It further focuses on issues of inter-professional collaboration between
public service professionals involved in services targeted at supporting children and young
people. This is significant at a time when the UK Government initiative, ‘Every Child Matters’,
seeks to ensure just such a collaboration. The work-in-progress reported here argues,
however, that such collaboration needs to be built upon an understanding of how intraprofessional
practices, within individual professions, work.


Abstract: Teachers work with a number of other professionals when supporting children
in their care. They also necessarily have to work with other teachers. This research note
reports the initial findings from two studies aimed at exploring the factors teachers
perceive to be significant when working with their colleagues. Study (1) involved an
opportunity interview sample of primary, secondary and special school teachers, working
predominantly in management positions or teaching in classrooms. Thematic coding,
informed by a grounded theory perspective, was used to analyse this data. Study (2)
involved semi-structured audio-taped interviews with 13 deputy-head teachers drawn
from primary, secondary and special school settings. Current work on the coding
structures, and categories needed to analyse this data in the light of the previous data,
are highlighted. As a result of the initial analysis, a need for a greater understanding of
the significance of intra-professional practices is identified. It is suggested that these
necessarily inform effective inter-professional collaboration.